The electrohydraulic method for meat tenderization and curing - N. A. Ermoshin; S. A. Romanchikov; O. I. Nikolyuk (Теория и практика переработки мяса, 2020)
The paper examines the problem of meat raw material curing in production of whole-piece meat products. The intensification methods for the process of penetration and distribution of curing ingredients throughout a product are described. Design of the equipment for meat tenderization URM-1 and URMP-1 is proposed, which ensure electrohydraulic tenderization of the structure of whole-piece (1500–2000 g) and portioned (80–120 g) meat semi-finished products and accelerate a process of brine distribution, which will allow reducing product strength characteristics by 51–53 kg/cm, reducing raw material losses, increasing labor productivity by 8–11%, shortening the duration of the technological process and reducing energy expenditure upon heat treatment by 18–20%. As a result of the experimental investigations, it was established that an electrohydraulic impact (frequency of pulses v = 0.5–1.0 pulse/sec., number of pulses from 150 to 200) can be used for tenderization of muscle connective tissue and tendons both of chilled (core temperature of 0 °C to 4 °C) and subfrozen (–2 °C to 3 °C) meat.